A Combination of Hermetia illucens Reared on Fish Waste and Poultry By-Product Meal Improves Sensory and Physicochemical Quality of Farmed Barramundi Filets - Chaklader, Md Reaz; Chung, Wing H.; Howieson, Janet; Fotedar, Ravi (Frontiers in Nutrition, 2022)
The proximate composition, sensory attributes and shelf life of fillets from barramundi, Lates calcarifer were fed a fishmeal (FM) based diet (0PBM-0HI) and three test diets replacing FM protein entirely with 85% poultry by-products meal (PBM) and 15% Hermetia illucens (HI) larvae meal protein (85PBM-15HI), 80% PBM and 20% HI (80PBM-20HI) and 75% PBM and 25% HI (75PBM-25HI) were investigated. After a 56-days feeding trial, crude protein, moisture, and ash percentage were unchanged while crude lipid increased in barramundi fillet when fed PBM-HI-based diets. The increase in C12:0 (lauric acid) and C14:0 (myristic acid) resulted in an increase in total saturated fatty acid while the monounsaturated fatty acid elevated due to an increase in C16:1n7 and C18:1cis+trans in the fillet of barramundi fed PBM-HI based diet. Whilst the decrease in total polyunsaturated fatty acid (PUFA) content in PBM-HI based fed barramundi fillet was mainly due to a decrease in essential fatty acid including C20:5n3 (eicosapentaenoic acid, EPA) and C22:6n3 (docosahexaenoic acid, DHA) when compared with the 0PBM-0HI fed barramundi fillet. The sensory quality was improved by PBM-HI-based diets, manifested by the highest scores given by the panellists. Texture profiles were not affected by diet but cohesiveness, gumminess, and chewiness decreased with increasing storage time. On days 1 and 8, skin brightness decreased in the skin of barramundi fed 85PBM-15HI and 80PBM-20HI compared to the skin of 0PBM-0HI fed barramundi. Skin redness improved in fish-fed PBM-HI-based diets. Flesh brightness and yellowness increased significantly in barramundi when fed PBM-HI based diets. On days 1 and 4, flesh brightness of barramundi fed PBM-HI based diets demonstrated an increase compared to 0PBM-0HI. PBM-HI diets suppress lipid oxidation while lipid oxidation increased over the storage time. In summary, the improvement in sensory quality and colour coupled with the suppression of rancidity in barramundi fillets underpinned the potentiality of using the mixture of PBM and HI transformed from food waste in the barramundi diet to improve the fillet quality and thus support sustainability and circular economy in aquaculture.